2016
DOI: 10.1002/adfm.201504839
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Self‐Assembly of Superparamagnetic Colloids under Magnetic Fields

Abstract: Self‐assembly processes are very important in material sciences but are particularly difficult to predict quantitatively. This is the case for particulate magnetic materials in which field‐induced self‐assembly processes are essential. This article describes the recent advances in the development of predictive theoretical tools for the study of directed self‐assembly of superparamagnetic colloids under magnetic fields. A practical view is presented of how to employ the new concepts (derived from thermodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 80 publications
2
114
0
Order By: Relevance
“…[11][12][13][14][15] More recently, some researchers have shown that more complex deposit structures can be achieved thanks to various concentrations of liquid crystals [16]. In this paper, we demonstrate that magnetic interactions between superparamagnetic colloidal particles [17][18][19][20][21] can be used to control the properties of colloidal droplets deposit, as illustrated in Fig.1. This actually requires the right chemical composition of the suspension.…”
Section: Introductionmentioning
confidence: 51%
“…[11][12][13][14][15] More recently, some researchers have shown that more complex deposit structures can be achieved thanks to various concentrations of liquid crystals [16]. In this paper, we demonstrate that magnetic interactions between superparamagnetic colloidal particles [17][18][19][20][21] can be used to control the properties of colloidal droplets deposit, as illustrated in Fig.1. This actually requires the right chemical composition of the suspension.…”
Section: Introductionmentioning
confidence: 51%
“…When submitted to a magnetic field, the magnetic energy per particle is much larger than the thermal energy and thus the magnetic forces can overcome Brownian motion to get the particles aligned into columns along the direction of the magnetic field (Figure c and Figure S5, Supporting Information) . This is observed both for the γ‐Fe 2 O 3 /silica and ε‐Fe 2 O 3 /silica particles.…”
Section: Resultsmentioning
confidence: 93%
“…where θ is the angle between the external field and the line joining the sphere centres [43,44]. Interestingly, a dual application of electric and magnetic fields on superparamagnetic particles allows the formation of birectional chains, colloidal networks and crystals by modulating the electric field and by keeping uniform the magnetic field [45].…”
Section: Magnetic Forcesmentioning
confidence: 99%